Structural properties of an S-system model of mycobacterium tuberculosis gene regulation - Farinas, Honeylou F.; Mendoza, Eduardo R.; Lao, Angelyn R. (2020)
Magombedze and Mulder (2013) studied the gene regulatory system of Mycobacterium tuberculosis (Mtb) by partitioning this into three subsystems based on putative gene function and role in dormancy/latency development. Each subsystem, in the form of S-system, is represented by an embedded chemical reaction network (CRN), defined by a species subset and a reaction subset induced by the set of digraph vertices of the subsystem. For the embedded networks of S-system, we showed interesting structural properties and proved that all S-system CRNs (with at least two species) are discordant. Analyzing the subsystems as subnetworks, where arcs between vertices belonging to different subsystems are retained, we formed a digraph homomorphism from the corresponding subnetworks to the embedded networks. Lastly, we explored the modularity concept of CRN in the context of the digraph. (Author's abstract)